2007
DOI: 10.1038/sj.ejcn.1602687
|View full text |Cite
|
Sign up to set email alerts
|

Association between the intake of vitamins and trace elements from supplements and C-reactive protein: results of the MONICA/KORA Augsburg study

Abstract: Objective: To examine the association between plasma concentrations of C-reactive protein (CRP) and the intake of vitamins and trace elements from supplements possibly related to inflammation such as vitamin C, vitamin E, carotenoids, selenium and zinc. Design: Cross-sectional study using data from the Monitoring of Trends and Determinants in Cardiovascular Disease/ Cooperative Health Research in the Region of Augsburg (MONICA/KORA) Survey 1994/95. Setting: Region of Augsburg, Southern Germany. Subjects: Popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
39
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 44 publications
(37 reference statements)
10
39
1
3
Order By: Relevance
“…A German study of the MONICA/KORA Augsburg cohort (23) reported an inverse association of vitamin E intake from supplements with plasma CRP concentrations but did not find an association with Se intake. However, the same study was not in accordance with our findings on vitamin C and carotene intakes.…”
Section: Discussionmentioning
confidence: 95%
“…A German study of the MONICA/KORA Augsburg cohort (23) reported an inverse association of vitamin E intake from supplements with plasma CRP concentrations but did not find an association with Se intake. However, the same study was not in accordance with our findings on vitamin C and carotene intakes.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, some investigations have linked serum selenium concentrations with inflammatory biomarkers such as CRP, suggesting circulating CRP as a negative predictor of serum selenium (Ghayour-Mobarhan et al, 2005). On the other hand, vitamin and mineral supplementation is associated with lower concentrations of CRP in women, specially with selenium and vitamin E supplementation (Scheurig et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the intake of selenium and other antioxidants has been associated with lower C-reactive protein (CRP) in women, suggesting a possible anti-inflammatory role for antioxidant nutrients (Scheurig et al, 2007). Furthermore, a high selenium intake has been proposed to reduce the risk of diseases induced by oxidative stress and inflammation (Ferencik and Ebringer, 2003) and has been related to changes in lipid metabolism (Bleys et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the observational studies, some trials have investigated the effect of supplementation with antioxidant nutrients on inflammatory biomarkers, with somewhat inconsistent results [29,30,31,32,33,34,35,36]. A meta-analysis of the results of supplementation trials with antioxidant nutrients conducted in healthy populations concluded that supplementation did not significantly reduce CRP levels [29].…”
Section: Discussionmentioning
confidence: 99%